2014
DOI: 10.1002/mds.26087
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional connectivity of the amygdala is associated with depression in Parkinson's disease

Abstract: Depressive symptoms are common in Parkinson's disease (PD), but the pathophysiology and neural basis underlying depression in PD is not well understood. Abnormal functional connectivity of the amygdala with various cortical and subcortical areas has been observed in major depressive disorder, indicating that dysfunction of the corticolimbic network may be involved in the pathogenesis of major depressive disorder. However, little is known about alterations of amygdala functional connectivity in depressed PD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 46 publications
7
72
0
Order By: Relevance
“…[8,10,11] Furthermore, the current study has extended the previous studies by identifying the aberrant interactions among MN, EN, DMN, and DAN in DPD. These results provide new evidence for the notation that DPD can be characterized as a functional disconnection syndrome.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…[8,10,11] Furthermore, the current study has extended the previous studies by identifying the aberrant interactions among MN, EN, DMN, and DAN in DPD. These results provide new evidence for the notation that DPD can be characterized as a functional disconnection syndrome.…”
Section: Discussionsupporting
confidence: 60%
“…All these previous studies focus on regional deficits [8] and/or functional connectivity abnormalities of a specific network. [9–11] These results revealed impairments of many brain regions in the motor network, default mode network, and emotion network as well as many functional pathways among these networks in DPD patients, as compared with non-depressed PD (NDPD) and normal controls (NC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral decreases in regional cerebral blood flow of the medial prefrontal cortex is also a common finding in PD patients with depression 56. Abnormal functional connectivity of the amygdala, the prefrontal-limbic system, the prefrontal cortex, and the lingual gyrus was associated with depressive symptoms in PD patients;57,58 however, a study found intact limbic-prefrontal connections54 in a similar group of patients. Furthermore, depression in PD is also related to gray and white matter volume deterioration in the orbitofrontal and temporal regions as well as in the cortical-limbic system 59–61.…”
Section: Depression In Untreated Pdmentioning
confidence: 99%